The Implementation of Reciprocal Method towards the Students' Reading Comprehension at the Second Grade of Junior High School - Kusriandi, Wendi; Kusuma, Tiara Putri (Universitas Swadaya Gunung Jati, 2014)
The background of this research was based on problems that faced by students in reading class.The use of Reciprocal Method can be used as a teaching method to help teacher in teaching learning, especially in teaching reading comprehension. The study is aimed at responding the following question: 1) How is the implementation of reciprocal method in teaching reading comprehension?, 2)Is reciprocal method effective for students in learning reading comprehension. This research was conducted by using quasi experimental method.The method of the research was quantitative and qualitative. Data were obtained by giving test to the students of second grade (VIII C as experimental Group and VIII E as control group). The instruments that were used to collect data were pre-test and post-test as main instrument and questionnaire as second instrument. The test was used to know students' ability in reading comprehension before and after the teacher implementing Reciprocal Method. Questionnaire was used to know students' perception during teaching learning process. The data for this experimental study were students' reading pre-test post-test scores and students' activites results, and the reading scores were analyzed with Fraenkle and Wallen formula. The result of t is 6,6 t is 1,997 for α = 5%. So the account table conclusion is t is higher than t (t > t ). The research found that the reading account table account table scores of the experimental group is higher than the control group and it is also supported by the students' perception.Furthermore, the students' perception results indicate that there were positive responses towards the use of Reciprocal Method in teaching reading. It was effective both in arousing students' motivation and in improving their reading comprehension. From the results, using Reciprocal Method in teaching reading comprehension was expected to be a new contribution for helping teacher to conduct an effective and interesting learning in the classroom.